2016
DOI: 10.1104/pp.15.01971
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Experiments across Diverse Environments Identifies the Genetic Determinants of Variation in Sorghum bicolor Seed Element Composition

Abstract: Seedling establishment and seed nutritional quality require the sequestration of sufficient element nutrients. The identification of genes and alleles that modify element content in the grains of cereals, including sorghum (Sorghum bicolor), is fundamental to developing breeding and selection methods aimed at increasing bioavailable element content and improving crop growth. We have developed a high-throughput work flow for the simultaneous measurement of multiple elements in sorghum seeds. We measured seed el… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 62 publications
6
61
0
Order By: Relevance
“…Single seeds were profiled for the quantities of 20 elements using ICP-MS. These measurements were normalized to seed weight and technical sources of variation using a linear model, with the resulting values used as the elemental traits for all analyses (Shakoor et al 2016). After outlier removal, seed element phenotypes were derived by averaging line replicates (kernels subsampled out of pooled ears from a row) within an environment.…”
Section: Resultsmentioning
confidence: 99%
“…Single seeds were profiled for the quantities of 20 elements using ICP-MS. These measurements were normalized to seed weight and technical sources of variation using a linear model, with the resulting values used as the elemental traits for all analyses (Shakoor et al 2016). After outlier removal, seed element phenotypes were derived by averaging line replicates (kernels subsampled out of pooled ears from a row) within an environment.…”
Section: Resultsmentioning
confidence: 99%
“…The second reason for thinking carefully about phenotype is because the probability of GWAS succeeding is directly related to the number and effect sizes of genes responsible for variation: The fewer the genes and the larger the effects, the more power for identifying the genes. Consistent with the expectation that it is easier to identify loci underlying variation in traits with a simple genetic basis, some of the strongest statistical signals are for metabolic traits for which there is a single enzyme or transporter that is responsible for distinct phenotypes (Lipka et al., ; Chen et al., ; Matsuda et al., ; Strauch et al., ; Shakoor et al., ). By contrast, we should not expect GWAS to provide extremely strong signals for genes that contribute to variation in highly complex multigenic quantitative traits such as height.…”
Section: The Importance Of Phenotype: Picking Traits and Minimizing Amentioning
confidence: 87%
“…A total of 265,487 SNPs based on genotype-by-sequencing (GBS) analyses that corresponds to variation in 27,412 annotated genes were utilized [33]. Previous studies demonstrated that this panel and genotype data has sufficient power to dissect complex traits using such populations, including grain yield [62], plant architecture [63] and seed micronutrient composition [64] among other traits.…”
Section: Methodsmentioning
confidence: 99%